The Mark of Postmodernism: Reading Roger Rabbit - Silverman, Hugh (Cinémas, 1995)
Who Framed Roger Rabbit? (Zemeckis, 1988) beats the traces of postmodernity. Behind this simple animation film and its spectacular technology, behind these drawings of a cute little alcoholic rabbit anxious about the intentions of his voluptuous wife, lurks an "epistemological rupture." The author demonstrates how the film is caught up in a game of boundaries, conventions and genres transgressed, in multiple folds of codes looping back on themselves, in reiterations of ironic quotes. He shows how Roger Rabbit might be considered an obsolete figure transformed into a postmodern hero.